2021
DOI: 10.1155/2021/8427150
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Treated and Untreated Subclinical Hypothyroidism on Metabolic Profile in Women with Polycystic Ovary Syndrome

Abstract: Background. Polycystic ovary syndrome (PCOS) and hypothyroidism are the most common endocrinological disorders among women of reproductive age. Since hypothyroidism occurs more frequently in PCOS patients, it is vital to explain its clinical impact. Aim. To evaluate the impact of subclinical hypothyroidism (SCH) and its treatment on the metabolic profile of patients with PCOS. Methods. 190 women with PCOS phenotype A were enrolled in the case-control study. They were divided into three groups: 38 women with PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Glintborg, D. et al found an increased risk of hypothyroidism, Graves' disease, goiter, and thyroiditis in the Danish population with PCOS [3]. Similar ndings have been found in many studies [4][5][6][7][8][9]. A recent large sample meta-analysis study [10,11] also revealed a strong association between thyroid disease and PCOS.…”
Section: Introductionsupporting
confidence: 62%
“…Glintborg, D. et al found an increased risk of hypothyroidism, Graves' disease, goiter, and thyroiditis in the Danish population with PCOS [3]. Similar ndings have been found in many studies [4][5][6][7][8][9]. A recent large sample meta-analysis study [10,11] also revealed a strong association between thyroid disease and PCOS.…”
Section: Introductionsupporting
confidence: 62%
“…Another study conducted in 2012 [16], which included 20 women with PCOS and SCH and 39 women with PCOS and euthyroid status, revealed significantly elevated fasting insulin levels and HOMA-IR values. A more recent cross-sectional study (2018), which included 137 females diagnosed with PCOS and having SCH, revealed impaired fasting plasma glucose (FPG) and impaired insulin sensitivity [15].…”
Section: Review Insulin Resistancementioning
confidence: 98%
“…Insulin resistance is more common among women with SCH than those without SCH [ 15 ], which reveals some association between SCH and insulin resistance; however, the exact mechanism of which is not clear. A significant dependence between TSH value and insulin resistance has been described by Mueller et al [ 14 ] in women with PCOS, irrespective of their BMI [ 16 ]. The Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) is an insulin resistance index used to determine a person's chances of developing diabetes; it has been well documented by Mueller et al in 2009.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the gradual improvement of people's living standards and changes in dietary structure in China, dyslipidemia has become one of the major diseases threatening the health of middle-aged and elderly people, and is the main cause of atherosclerosis (AS) and coronary heart disease (CHD), damaging the health of patients ( 2 ). Lipid metabolism disorders often emerge with diseases such as obesity, diabetes, and ovarian syndrome, causing complex effects on the human body ( 3 ). Therefore, it is clinically important to seek treatments that effectively regulate the disorders of lipid metabolism and prevent the occurrence of dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%